Hubungan Faktor Lingkungan Fisik Rumah dan Respons Terhadap Praktik Pengobatan Strategi DOTS Dengan Penyakit Tb Paru di Kecamatan Tirto Kabupaten Pekalongan Tahun 2010 - Setiawan Dwi Antoro; Onny Setiani; Yusniar Hanani Darundiati (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background : Pulmonary tuberculosis caused by Mycobacterium tuberculosis, the prevalence rate of tuberculosis cases in the year 2009 in the district Pekalongan of sub district Tirto 96/100.000%. In the last 3 years from 2007 until 2009 the average monthly case found 9 cases of pulmonary tuberculosis. Condition of housing residents who qualify as a healthy house has just reached 49%, has not met the target Ministry of Health, by 80%. This research was to analyze the association between, physical environmental and response to treatment practices with the DOTS strategy of TB pulmonary disease in sub district Tirto Pekalongan District year of 2010. Method : The type of this study is observational analytic study using case control study. Subjects of this study 106 people, consisting of 53 cases and 53 controls. The data were analyzed with chi-square test to determine the description and the relationship of risk factors with disease incidence of tuberculosis (univariate and bivariate analysis), then performed multivariate analysis with logistic regression. Result : The bivariate analysis result found that related to pulmonary tuberculosis were: type of floor in the house (ρ-value = 0.001), type of wall in the house (ρ-value = 0.001), index of ventilation in the house (ρ-value = 0.028), index of ventilation in bedroom (ρ-value = 0.039), ventilation in (stack hole) the kitchen/separation of kitchen and the main house (ρ-value=0.001), solar orientation (natural lighting) in house (p-value =0.025), solar orientation (natural lighting) in bedroom (p-value = 0.020), humidity room in the house (p-value =0.047), density of occupants in the house (p-value = 0.028) and the density of occupants in bedroom (p-value =0,045), knowledge level (p-value =0.014) nutritional status (p-value = 0.002), and response to treatment practices strategy with DOTS (p-value = 0.031).While the results of multivariate analysis are shown as risk factors for disease incidence of tuberculosis were ventilation in (stack hole) the kitchen/ separation of kitchen and the main house (OR= 6.824), type of floor in the house (OR= 3.860), type of house walls (OR =4.138), density of occupancy in bedroom (OR= 2.514), and response to TB treatment practices strategy with the DOTS (OR=2.606). Conclusion :  there are five variable significant related to tuberculosis were ventilation in (stack hole) the kitchen/ separation of kitchen and the main house, the type of floor, wall type, occupant density in bedroom and response to TB treatment practices strategy with the DOTS of proven associated with disease incidence of tuberculosis. Keywords: Physical environmental of housing factors, ), Pulmonary tuberculosis, Sstrategy Directly Observed Treatment Short-course (DOTS)